1980 19th IEEE Conference on Decision and Control Including the Symposium on Adaptive Processes 1980
DOI: 10.1109/cdc.1980.271808
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal control strategies for multilocomotive powered trains

Abstract: Thin pcper introduces two different controllers for the handling of very long dripovered trains, including braking operati-. The deviations f r a r e f e r e n c e v a l u e due to grade changes and other pmpose of the controller is to minimize coupler force and v e l o c i t y disturbances. The controller is nuperi.lposed t o a throttling and brakin8 schedule known beforehand. As there a r e ConstrnintB on the inputs (especially the braking inputs) and the coupler forces that c-t be neglected, a linear contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Research based on the cascade-mass-point model, therefore, has become a new trend in recent years. Gruber and Bayoumi 10 investigated the longitudinal dynamics of multi-locomotive powered train and approximated it as a nonlinear mass-spring dashpot model which was interconnected via couplers at the first time. They demonstrated that this method could efficiently minimize the coupler forces which resulted in safer operation and increased traveling speeds.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Research based on the cascade-mass-point model, therefore, has become a new trend in recent years. Gruber and Bayoumi 10 investigated the longitudinal dynamics of multi-locomotive powered train and approximated it as a nonlinear mass-spring dashpot model which was interconnected via couplers at the first time. They demonstrated that this method could efficiently minimize the coupler forces which resulted in safer operation and increased traveling speeds.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Gruber and Bayoumi [65] created a train controller to minimize the difference from a given speed profile while also minimizing coupler force. This study first simplified the train model by linearizing connections between wagons and by combining multiple wagons into groups.…”
Section: Open-loop and Closed-loop Controllersmentioning
confidence: 99%
“…In this study, the cascade mass point train model which was presented in [12] and validated in [13] is adopted. Taking advantage of this model, the train's in-train dynamics are taken into consideration.…”
Section: Introductionmentioning
confidence: 99%